Three-dimensional structure-activity relationship study of belactosin A and its stereo- and regioisomers: development of potent proteasome inhibitors by a stereochemical diversity-oriented strategy - Yoshida, Keisuke; Yamaguchi, Kazuya; Mizuno, Akira; Unno, Yuka; Asai, Akira; Sone, Takayuki; Yokosawa, Hideyoshi; Matsuda, Akira; Arisawa, Mitsuhiro; Shuto, Satoshi (Organic & biomolecular chemistry, 2009)
The development of potent proteasome inhibitors based on the stereochemical diversity-oriented strategy using a conformationally rigid cyclopropane structure was investigated. Thus, a series of stereo- and regioisomeric analogs of belactosin A (2), a cyclopropane amino acid (methanoamino acid)-containing tripeptidic proteasome inhibitor, were designed, in which the central cyclopropane amino acid part was replaced with the corresponding stereo- or regioisomer. Using a series of stereoisomeric cyclopropane amino acid equivalents with the cis/trans, D/L, and syn/anti stereochemical diversity, which were previously developed by us, as key units, the target compounds were successfully synthesized. Biological evaluation showed that, as expected, compound activity changed depending on the stereochemistry of the central cyclopropane amino acid part: the trans/L-syn-isomer 7 and the cis/L-anti-isomer 9 were more than twice as potent as natural belactosin A (trans/L-anti-isomer). Furthermore, the tripeptidic compound 13, the synthetic precursor for the unnatural cis/L-anti-isomer 9, was identified as a highly potent proteasome inhibitor. This compound, which is 20 times as potent as belactosin A and is even more potent than the well-known inhibitor lactacystin (4), may be an effective lead for developing clinically useful anticancer drugs. These results show that the stereochemical diversity-oriented approach can be a powerful strategy for the development of highly active compounds in medicinal chemical studies.